2022
DOI: 10.3390/jcm11123468
|View full text |Cite
|
Sign up to set email alerts
|

Bridge Nodes between Personality Traits and Alcohol-Use Disorder Criteria: The Relevance of Externalizing Traits of Risk Taking, Callousness, and Irresponsibility

Abstract: Background: Personality disorders show strong comorbidities with alcohol-use disorder (AUD), and several personality traits have been found to be more frequent in people with AUD. This study analyzes which personality facets of those proposed in the Alternative Model of Personality Disorder (AMPD) of DSM-5 are associated with the diagnostic criteria of AUD. Methods: The sample was composed of 742 participants randomly selected from the Spanish population, and 243 patients attending mental health services. All … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 51 publications
(66 reference statements)
0
0
0
Order By: Relevance
“…Importantly, relation of traits with mental health outcomes should be further considered. Phenotypic relationships between these symptoms and traits have also been evidenced on variable-centered approaches through factor analyses studies (Markon, 2010) and by empirical networks' evidence (Borsboom & Cramer, 2013;De la Rosa et al, 2022), and was integrated into theoretical models such as the Hierarchical Taxonomy of Psychopathology (HiTOP; Kotov et al, 2017). The aforementioned study by Rossi et al (2021), showed that the Resilient type showed less pathology than the other types, Overcontrolled profiles had a higher prevalence of mood disorders, while the Undercontrolled exhibited higher scores on borderline and narcissistic scales.…”
Section: Introductionmentioning
confidence: 97%
“…Importantly, relation of traits with mental health outcomes should be further considered. Phenotypic relationships between these symptoms and traits have also been evidenced on variable-centered approaches through factor analyses studies (Markon, 2010) and by empirical networks' evidence (Borsboom & Cramer, 2013;De la Rosa et al, 2022), and was integrated into theoretical models such as the Hierarchical Taxonomy of Psychopathology (HiTOP; Kotov et al, 2017). The aforementioned study by Rossi et al (2021), showed that the Resilient type showed less pathology than the other types, Overcontrolled profiles had a higher prevalence of mood disorders, while the Undercontrolled exhibited higher scores on borderline and narcissistic scales.…”
Section: Introductionmentioning
confidence: 97%
“…This may be specifically useful in the comorbidity between SUD and personality disorders. The research by De la Rosa-Cáceres et al [10] focused on the study of the personality facets of the Alternative Model of Personality Disorder of DSM-5 [11] in patients with alcohol use disorder by means of a network analysis. The data show a connection with the facets related to the disinhibition (risk taking, irresponsibility, impulsivity, and rigid perfectionism) and antagonism (callousness, grandiosity, and hostility) domains, which are also associated with premature patient dropout.…”
mentioning
confidence: 99%